APLIKASI INVERS SEMU (PSEUDOINVERSE) DENGAN METODE GREVILLE’S PADA ANALISIS REGRESI LINEAR BERGANDA - Muhtar Safi’i; Khurul Wardati; Mohammad Farhan Qudratullah (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
Concept of matrix inverse is limited to ???? × ???? singular matrix. Matrix with ???? × ???? or ???? × ???? a singular concept of inverse matrix solved with pseudoinvers. Pseudoinverse ???? symbol is a matrix ???? of any matrix ???? that meet the 4 traits, namely: ???????????? = ????, ???????????? = ????, ???????? = ????????, (????????)∗ = ????????, where ( )∗ is the conjugate transpose notation. One of method to find pseudoinverse is Greville's method. A Greville’s method is finite iterating method that uses matrix partitions. The amount of iterations this method until ???? columns of the matrix inverse to search all pseudoinverse. This research will discuss the application and the properties of the estimators of regression coefficients in the multiple linear regression.